Relationship Between Prolonged Intraocular Inflammation and Macular Edema After Cataract Surgery - Aaronson Alexander; Taipale Claudia; Achiron Asaf; Aaltonen Vesa; Grzybowski Andrzej; Tuuminen Raimo (Association for Research in Vision and Ophthalmology, 2022)
Purpose
To assess whether aqueous flare is related to an increased risk of pseudophakic cystoid macular edema (PCME) following uneventful cataract surgery in nondiabetic and diabetic patients.
Methods
A post hoc analysis of five consecutive randomized clinical trials in the Department of Ophthalmology, Kymenlaakso Central Hospital, Finland. Aqueous flare levels were recorded in 448 eyes of 448 patients before surgery, and after the course of topical anti-inflammatory treatment 28 days and three months after cataract surgery.
Results
Aqueous flare increase of <50%, ≥50%, ≥100%, and ≥200% associated in central subfield macular thickness (CSMT) increase across the groups at 28 days and three months after surgery. Increase of aqueous flare ≥100% compared to those with <100% was associated with increased CSMT (P = 0.022 at 28 days, and P = 0.027 at three months). At three months, macular thickening (at least 10% CSMT increase) was observed in 12.7% compared to 4.6% of eyes when using a cutoff value of 100% increase in aqueous flare (P = 0.033). Although diabetic patients presented higher aqueous flare levels at baseline compared to nondiabetic patients (12.9 ± 11.8 vs. 9.8 ± 8.2 photon units/ms P < 0.001), the postoperative levels illustrated a similar profile in aqueous flare increase between the two groups.
Conclusions
At 28 days, aqueous flare increase was associated with macular thickening. A 100% cutoff value could potentially be used when studying anti-inflammatory efficacy of different treatment protocols. Flare values exceeding this cutoff value could be considered as an indication for extending anti-inflammatory therapy.
Translational Relevance
A 100% increase in aqueous flare at 28 days after cataract surgery from baseline predicted macular thickening up to three months postoperatively. Identifying a correlation between increased aqueous flare levels and pseudophakic cystoid macular edema may allow recognition of the most vulnerable patients, development of prophylactic treatment strategies and reduction of the number and severity of postoperative complications.